2004
DOI: 10.1375/brim.5.1.12.35399
|View full text |Cite
|
Sign up to set email alerts
|

Community Integration Following Severe Traumatic Brain Injury: Outcomes and Best Practice

Abstract: Community integration is often cited as the ultimate aim of rehabilitation. However, outcome studies show that following severe traumatic brain injury (TBI), many people do not return to valued life roles or reach previous levels of integration within their community. More recent research, in association with extensive clinical experience, reveals significant variability in outcomes within this group. Although some people return to productive activity and maintain a network of family and friends, others lead l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 38 publications
0
39
0
Order By: Relevance
“…A significant behavioral deficit experienced by persons with ABI is often the decreased initiation of purposeful activity that may be especially important during leisure time (Davis & Chittum, 1994). There are several studies indicating that people with a brain injury are often unable to return to previous leisure activities and have fewer interests than they did prior to their injury (Brown & Vanderdergoot, 1998;Sloan, Winkler, & Callaway, 2004). People with a brain injury also tend to be involved in less physical and more passive recreation than previously, and it has been suggested that depression and fatigue play a role in this reduced involvement (Brown, Gordon, & Spielman, 2003).…”
Section: Impact Of Abi On Leisure Participationmentioning
confidence: 99%
“…A significant behavioral deficit experienced by persons with ABI is often the decreased initiation of purposeful activity that may be especially important during leisure time (Davis & Chittum, 1994). There are several studies indicating that people with a brain injury are often unable to return to previous leisure activities and have fewer interests than they did prior to their injury (Brown & Vanderdergoot, 1998;Sloan, Winkler, & Callaway, 2004). People with a brain injury also tend to be involved in less physical and more passive recreation than previously, and it has been suggested that depression and fatigue play a role in this reduced involvement (Brown, Gordon, & Spielman, 2003).…”
Section: Impact Of Abi On Leisure Participationmentioning
confidence: 99%
“…The priorities include the opportunity to obtain a residence, maintain a social support network and engage in productive activity. However, after traumatic brain injury many individuals are unable to attain a sense of belonging and high quality of life standards (Sloan et al, 2004;Minnes et al, 2003). In addition return to work is often cited as an objective indicator of CI even though many persons do not return to work.…”
Section: Definition Of Community Integrationmentioning
confidence: 99%
“…disability, pathways of care, and outcomes (Abreu et al, 1996;Abreu and Peloquin, 2005;Doig et al, 2001;Heubner et al, 2003;Sloan et al, 2004). This adaptable rehabilitation process has been described by the type of facility and level of care provided ranging from intensive care units, where the person with brain injury is provided with life-sustaining medical care, to CI programmes generally focused on helping individuals participate fully within society (Abreu and Peloquin, 2005;Doig et al, 2001;Gutman, 1999).…”
mentioning
confidence: 99%
“…The broad aim of community-based rehabilitation following acquired brain injury (ABI) is to maximize community integration and quality of life by facilitating greater independence, choice, opportunity and access to appropriate services for these individuals and their families [1][2][3]. The need for community-based services to enhance long-term outcomes has been highlighted by studies suggesting that psychosocial functioning may not improve and can even deteriorate over time [4,5].…”
Section: Introductionmentioning
confidence: 99%